Potential Efficiency Gains from Consolidation of Maine’s Educational Resources - Trostel, Philip (Maine Policy Review, 2003)
Economist Philip Trostel analyzes the size of Maine’s schools and school districts and the costs and quality of education. He argues that some schools and districts may be too small to be cost-efficient; that on average education in Maine costs more per student than in the rest of the country; and that education quality may not be as high in smaller schools as in larger ones, at least based on some measures. While there may be some less-measurable benefits to small schools, Trostel suggests that declining school-age populations and increasing costs should lead policymakers to seriously consider consolidating schools and districts, not only to achieve cost savings but also to enable more opportunities for Maine’s children.